Development of a Basic Literacy-Based Flipbook to Improve Reading Comprehension of Narrative Texts in Higher Grades - Rizki, Daniatur; Purwati, Panca Dewi (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This study addresses the critical challenge of low reading comprehension among elementary school students by developing and evaluating a Basic Literacy-Based Flipbook. Employing a Research and Development (R&D) methodology based on the modified Borg and Gall model, the study aimed to design, validate, and test the effectiveness of a basic literacy-based flipbook integrating local Semarang culture. The research was conducted in two phases: a small-scale test with six students at Pakintelan 01 Public Elementary School and a large-scale test with 28 students at Bringin 1 Public Elementary School, Semarang. The flipbook was designed based on the results of the analysis of potential and identifying problems, and was validated by expert validators. The media expert rated the product with an initial feasibility score of 84.72%, which increased to 91.66% after revision, while the material expert gave it a 90% score, confirming the product's very feasible criteria. In the effectiveness test, the small-scale group's average pre-test score of 56 increased to 82 in the post-test, and the large-scale group's pre-test average of 57.6 rose to 83.5. N-gain scores of 62.3% for the small scale and 61% for the large scale indicate that the media is